Critical effect of nanometer-size surface roughness of a porous Si seed layer on the defect density of epitaxial Si films for solar cells by rapid vapor deposition. Issue 13 (15th February 2018) - Hasegawa, Kei; Takazawa, Chiaki; Fujita, Makoto; Noda, Suguru; Ihara, Manabu
Abstract : Monocrystalline, low defect Si thin films fabricated via 1-minute vapor deposition on a double porous layer treated by zone heating recrystallization. Abstract : Monocrystalline, low-defect density Si thin films were successfully fabricated via epitaxy with 1 minute rapid vapor deposition on a porous seed layer. Zone heating recrystallization reduced the surface roughness of the seed layer to sub-nanometer size. The critical effect of roughness on the defect density of epitaxial films was confirmed.